PEMBERDAYAAN MASYARAKAT MELALUI EDUKASI LITERASI KEUANGAN KELUARGA DI DESA WAKAL KABUPATEN MALUKU TENGAH - Lewaru, Trisna Sary; Basuki, Ferry H; Soepriadi, Dewi N; Leiwakabessy, Theofilia F F; Laitupa, Muhammad F; Sitanala, Theresia F; Temalagi, Selva; Kriswantini, Dwi; Engko, Cecilia; Lenggono, Tirza O; Pattinaja, Elna M (Universitas Pattimura, 2022)
The implementation of this community service aims to provide education on family financial literacy. This activity was carried out in Wakal Village, Leihitu District, Central Maluku, on Saturday, June 4, 2022, at 10.00 WIT. The implementation is in collaboration with students of pattimura university real work lectures placed in the village. This community empowerment event was attended by housewives and the public of Wakal Village, totaling 20 people. This activity received a good response from participants because this family financial literacy education has only been carried out in the village and it is hoped that activities like this can continue